2011
DOI: 10.2174/1874213001003020068
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses of Quantitative Climate Reconstructions Based on Late-Quaternary Biological Proxies

Abstract: Abstract:The importance of reconstructing past environments quantitatively in palaeoecology is reviewed by showing that many ecological questions asked of palaeoecological data commonly involve the reconstructions of past environment. Three basic approaches to reconstructing past climate from palaeoecological data are outlined and discussed in terms of their assumptions, strengths, and weaknesses. These approaches are the indicator-species approach involving bioclimateenvelope modelling; the assemblage approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
284
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(300 citation statements)
references
References 370 publications
(638 reference statements)
4
284
0
Order By: Relevance
“…Biological proxies remain important in all settings, for example indicator species of wetlands, seagrass, or ice cover and multispecies "transfer functions" used to infer temperature and salinity (57). However, as with niche models that use present-day bioclimatic associations to anticipate the future redistribution of species (see paleontologic tests of their reliability by refs.…”
Section: Proxy Evidence Of (Paleo)environmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological proxies remain important in all settings, for example indicator species of wetlands, seagrass, or ice cover and multispecies "transfer functions" used to infer temperature and salinity (57). However, as with niche models that use present-day bioclimatic associations to anticipate the future redistribution of species (see paleontologic tests of their reliability by refs.…”
Section: Proxy Evidence Of (Paleo)environmentalmentioning
confidence: 99%
“…However, as with niche models that use present-day bioclimatic associations to anticipate the future redistribution of species (see paleontologic tests of their reliability by refs. 58 and 59), there are concerns that the transfer-ecology approach is vulnerable to (i) failure of observed species' distributions to reflect their full tolerances, (ii) inability to account for shifting biotic interactions and evolutionary adaptation, and (iii) assumptions of the statistical methods used (57,60). Analysis of paleo-environmental conditions, including pollution and many aspects of ecosystem structure, has thus shifted increasingly from taxonomic to other biological, physical, and especially chemical evidence [isotopic and elemental ratios; environmental aDNA; molecular biomarkers of metabolism and organic-matter source; and indicator minerals of oxidation potential (Eh), pH, and salinity], achieving a new level of independence from ecological assumptions and expanding the dimensions of inference (e.g., refs.…”
Section: Proxy Evidence Of (Paleo)environmentalmentioning
confidence: 99%
“…Testate amoebaebased hydrological transfer functions have been developed in many parts of the world; Alaska (Markel et al, 2010;Payne et al, 2006), Canada (Charman and Warner, 1997;Warner and Charman, 1994), Europe , Greece (Payne and Mitchell, 2007), New Zealand (Charman, 1997;Wilmshurst et al, 2003), North America (Booth, 2008;Booth and Zygmunt, 2005), Northern Ireland ), Switzerland (Mitchell et al, 1999), Poland (Lamentowicz et al, 2008;Lamentowicz and Mitchell, 2005), and the United Kingdom (Woodland et al, 1998). Due to spatial autocorrelation (Borcard et al, 1992;Lennon, 2000), transfer functions require validation against data sets that are completely independent of the training set (Belyea, 2007;Birks et al, 2010). However, very few models are rigorously tested using spatially independent data and it has been suggested that they may generate reconstructions of unrealistic accuracy Telford and Birks, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the four types of pollen traps always yield different pollen assemblages even if they are collected from the same site (e.g., Fall, 1992;Wilmshurt and McGlone, 2005a;Lisitsyna et al, 2012;). Consequently, many palynologists (e.g., Seppa et al, 2004;Birks et al, 2010) emphasize that the modern pollen calibration set for quantitatively reconstructing palaeoclimate should be established based on the pollen data from surface lake sediments because most fossil pollen data are extracted from lacustrine sediments (such as lake cores).…”
mentioning
confidence: 99%